Tris(o-phenylenedioxy)cyclotriphosphazene as a Promoter for the Formation of Amide Bonds Between Aromatic Acids and Amines - Movahed, Farzaneh Soleymani; Sawant, Dinesh N.; Bagal, Dattatraya B.; Saito, Susumu (Synthesis, 2020)
The atom-efficient formation of amide bonds has emerged as a top-priority research field in organic synthesis, as amide bonds constitute the backbones of proteins and represent an important structural motif in drug molecules. Currently, the increasing demand for novel discoveries in this field has focused substantial attention on this challenging subject. Herein, the degradable 1,3,5-triazo-2,4,6-triphosphorine (TAP) motif is presented as a new condensation system for the dehydrative formation of amide bonds between diverse combinations of aromatic carboxylic acids and amines. The underlying reaction mechanism was investigated, and potential catalyst intermediates were characterized using 31P NMR spectroscopy and ESI mass spectrometry.
Keywords: amide bond formation; organophosphorus catalyst; dehydration; carboxylic acids; amines